The Role of The Voice of Indonesia As A Public Diplomic Media Through The Diplomatic Forum Event Program - Fornia Fornia; Arif Susanto (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Voice of Indonesia is part of institution broadcast public that owned by Radio of Republic Indonesia. Diplomatic Forum is one of Voice of Indonesia’s program. The concept of this program is talk show who talking about politic, economic and culture issues. The participant of this program are the ambbassador, part of the ministry or academics who expert in discussion topic. This research is to describe, analysis role of Voice of Indonesia through Diplomatic Forum Programme. This research is use by qualitative methods with constructivist paradigm. The result of this research taken by semi-structure interview and use literature study. The result of this research found that Diplomatic Forum Programme is one of Voice of Indonesia’s implementation from vision and mission Voice of Indonesia to become one of Instution owned by nation that can to build character nation and make positive image into foreign. Through diplomatic forum, foreigner listeners more understand about policies that apply in Indonesia thru the result of expert’s discussion in that programme and also help promote Indonesia into foreigners.